2008
DOI: 10.1038/oby.2008.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peroxisome Proliferator‐activated Receptor‐α Ligands in the Interaction Between Adipocytes and Macrophages in Obese Adipose Tissue

Abstract: objective: This study was designed to examine the effect of peroxisome proliferator-activated receptor-α (PPAR-α) ligands on the inflammatory changes induced by the interaction between adipocytes and macrophages in obese adipose tissue. Methods and Procedures: PPAR-α ligands (Wy-14,643 and fenofibrate) were added to 3T3-L1 adipocytes, RAW264 macrophages, or co-culture of 3T3-L1 adipocytes and RAW264 macrophages in vitro, and monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α) mRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
(83 reference statements)
4
21
0
1
Order By: Relevance
“…PPARa expression has been reported in adipose tissue (33,34), and preclinical data suggest a role of PPARa in body weight control, supporting the potential use of PPARa agonists in the treatment of obesity (35). A previous study demonstrated that PPARa ligand strongly inhibits atherosclerosis and attenuates macrophage-related inflammation in atherosclerotic foam cells (36); this was explained by the finding that PPARa activation decreases obesity-related adipose tissue inflammation (33,37). Additional studies are needed to explore the effect of telmisartan-induced PPARa activation on adipocytokines and inflammation in adipose tissue.…”
Section: Discussionmentioning
confidence: 92%
“…PPARa expression has been reported in adipose tissue (33,34), and preclinical data suggest a role of PPARa in body weight control, supporting the potential use of PPARa agonists in the treatment of obesity (35). A previous study demonstrated that PPARa ligand strongly inhibits atherosclerosis and attenuates macrophage-related inflammation in atherosclerotic foam cells (36); this was explained by the finding that PPARa activation decreases obesity-related adipose tissue inflammation (33,37). Additional studies are needed to explore the effect of telmisartan-induced PPARa activation on adipocytokines and inflammation in adipose tissue.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, evidence of fibrate antiinflammatory effects continues to emerge [20][21][22][23][24][25][26]. While Fig.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Interestingly, the activation of PPARa inhibits the expression of several genes involved in proinflammatory response in adipocytes including TNFa. 48,49 On the basis of this evidence, it is likely that the marked increase of TNFa detected in the AT of ATGL KO mice is also the consequence of impaired ATGL-mediated PPARa expression.…”
Section: Discussionmentioning
confidence: 99%